The proteome and transcriptome of the infectious metacyclic form of Trypanosoma brucei define quiescent cells primed for mammalian invasion. Issue 1 (4th August 2017) - Christiano, Romain; Kolev, Nikolay G.; Shi, Huafang; Ullu, Elisabetta; Walther, Tobias C.; Tschudi, Christian
Summary: The infectious metacyclic forms of Trypanosoma brucei result from a complex development in the tsetse fly vector. When they infect mammals, they cause African sleeping sickness in humans. Due to scarcity of biological material and difficulties of the tsetse fly as an experimental system, very limited information is available concerning the gene expression profile of metacyclic forms. We used an in vitro system based on expressing the RNA binding protein 6 to obtain infectious metacyclics and determined their protein and mRNA repertoires by mass‐spectrometry (MS) based proteomics and mRNA sequencing (RNA‐Seq) in comparison to non‐infectious procyclic trypanosomes. We showed that metacyclics are quiescent cells, and propose this influences the choice of a monocistronic variant surface glycoprotein expression site. Metacyclics have a largely bloodstream‐form type transcriptome, and thus are programmed to translate a bloodstream‐form type proteome upon entry into the mammalian host and resumption of cell division. Genes encoding cell surface components showed the largest changes between procyclics and metacyclics, observed at both the transcript and protein levels. Genes encoding metabolic enzymes exhibited expression in metacyclics with features of both procyclic and bloodstream forms, suggesting that this intermediate‐type metabolism is dictated by the availability of nutrients in the tsetse fly vector. Abstract : We used an in vitro system to obtain Trypanosoma brucei metacyclics and determined their protein and mRNA repertoires by mass‐spectrometry‐based proteomics and mRNA sequencing in comparison to non‐infectious procyclic trypanosomes. We show that metacyclics are quiescent cells, and we propose that the transition to this quiescent state is a factor in the choice of a 'minimalistic' metacyclic variant surface glycoprotein (VSG) expression site, because it requires fewer cellular resources for activation.